Teach Foundational Language Principles. - Ball, Thomas; Zorn, Benjamin (Communications of the ACM, 2015)
The article discusses the teaching of computer programming languages and their basic principles in colleges and universities. The authors argue that since new programming languages are continuously being developed, it is critical to teach students foundational language principles. These include garbage collection and structured programming. Other topics include domain-specific languages (DSLs), formal design languages, and general-purpose languages.